The Effectiveness of Head-To-Tail Method in Solving Challenging Physics Tasks - Sharifov, G. M. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2020)
The article deals with the effectiveness of Head-to-tail method for addition vectors. The empirical investigations were carried out at a specialized school. In the research, the number of respondents was 24. As a part of the experiments, it was conducted questionnaires among them and they were given pre-test and post-test, which consists of 12 questions. Statistical analysis was performed using SPSS software. A paired t-test was carried out on pre-test and post-test to determine the possible difference between them. According to the statistically analysed data, it was established that by using Head-to-tail method, students could understand and solve more complicated test task regarding the motion of an object under the many forces. It was concluded that this method could be the best way of solving the most challenging issues related to one or two-dimensional motion and it makes a significant contribution to the more in-depth adoption of the students' understanding of finding the direction of resultant force for numerous forces vectors.